Comparison Between Visual and Radiographic Methods Using ICDAS Criteria in Permanent Molars for Detection of Occlusal and Proximal Caries – A Comparative Study: Comparison of Visual and Radiographic ICDAS Methods - Nand, Vijai; Memon, Mahwish; Jafferi, Ali Asghar; Ali, Muhammad; Memon, Sadia; Aslam, Shuja (Pakistan Journal of Health Sciences, 2025)
Early detection of dental caries is critical for timely intervention and prevention of disease progression. The International Caries Detection and Assessment System (ICDAS) offers a standardized approach to evaluate caries through both visual and radiographic methods. Objectives: To compare between visual and radiographic methods using ICDAS criteria in permanent molars for detection of occlusal and proximal caries Methods: This comparative cross-sectional study was conducted at Liaquat University of Medical and Health Sciences (LUMHS) after ethical approval, using non-probability consecutive sampling to recruit 378 patients. Individuals aged 16–35 years with fully erupted, clinically intact permanent molars and no signs of periodontal disease were included. Participants were assigned to Group A (occlusal caries) or Group B (proximal caries), with 189 in each group. Caries were assessed visually and radiographically using ICDAS criteria, with scores 1–2 indicating initial and 3–6 indicating advanced lesions. Two calibrated examiners performed the evaluations. Results: There were no statistically significant differences in baseline demographics between the occlusal and proximal caries groups. The mean age was comparable (25.9 ± 6.5 vs. 26.1 ± 6.2 years, p=0.753), as was gender distribution (p=0.752). When comparing diagnostic methods, no statistically significant differences were observed between visual and radiographic ICDAS assessments for detecting initial or advanced caries in either group (all p>0.05), indicating comparable diagnostic performance. Conclusions: Visual and radiographic methods based on the ICDAS system were equally effective in identifying occlusal and proximal carious lesions in permanent molars.